2014
DOI: 10.1007/s10571-014-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic and Anti-oxidative Roles of Quercetin After Traumatic Brain Injury

Abstract: Experimental studies have demonstrated significant secondary damage (including cell apoptosis, blood-brain barrier disruption, inflammatory responses, excitotoxic damage, and free radical production) after traumatic brain injury (TBI). Quercetin is a natural flavonoid found in high quantities in fruits and vegetables, and may be a potential antioxidant and free radical scavenger. The purpose of this study was to determine the effects of quercetin on TBI-induced upregulation of oxidative stress, inflammation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 29 publications
1
50
1
Order By: Relevance
“…As reported, quercetin inhibits hydrogen peroxide-induced apoptosis in mesangial cells [34] and epithelial cells [35]. Quercetin was also known to inhibit apoptosis of neuronal cells caused by trauma brain injury [36]. However, quercetin frequently activates apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, quercetin inhibits hydrogen peroxide-induced apoptosis in mesangial cells [34] and epithelial cells [35]. Quercetin was also known to inhibit apoptosis of neuronal cells caused by trauma brain injury [36]. However, quercetin frequently activates apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is also evidence that quercetin metabolites reach the cerebrospinal fluid after peripheral treatment [6567]. Quercetin also induces neuroprotective effects via inhibition of oxidative stress and inflammation in a traumatic brain injury model was also demonstrated [68]. Considering the information described above, local actions of quercetin in the spinal cord could not be disproved.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated Quercetin as an antioxidant3949, anti-angiogenic5051, neuroprotective5253, and anti-apoptotic agent5455. In ocular studies, Quercetin has been found to be efficacious in cataract prevention56, retinal angiogenesis57, and oxidative damage in retinal pigment epithelium cells5859.…”
Section: Discussionmentioning
confidence: 99%